Method for modifying the hydrophobicity of catalyst surfaces and its use for the selective oxidation of co
Patent Information
- Application Number
- CN202510521681.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-24
- Publication Date
- 2026-10-27
AI Technical Summary
然而,目前的大部分疏水改性方法主要是在催化剂表面进行改性,难以避免的会覆盖催化剂表面的部分金属活性位点,导致催化剂活性降低
[0010]本申请利用上述低温疏水方法对Pt/Al2O3催化剂进行改性,提高了催化剂在低温段的CO转化率,改性的催化剂具有更高的活性以及使用寿命。
Smart Images

Figure BDA0005374146770000121 
Figure BDA0005374146770000131 
Figure BDA0005374146770000141
Abstract
Description
Technical Field
[0001] This application belongs to the field of catalysts, specifically relating to hydrophobic modification of catalysts for the selective oxidation of CO in hydrogen-rich atmospheres. Background Technology
[0002] Water is inevitably generated or used in chemical production, playing a variety of roles as a solvent, reactant, byproduct, catalyst, or proton transfer agent. As a solvent, water helps increase the hydrophilicity of the substrate, thereby promoting the reaction. For example, in the reaction of carbon monoxide with alcohols, water molecules help maintain the concentration of hydroxyl groups, driving the reaction towards the desired selective oxidation. However, studies have also shown that water molecules can adsorb onto the catalyst surface, shielding the active sites of the metal, leading to catalyst deactivation, and even causing side reactions and reducing yield. Noble metals such as Pt and Pd are prone to aggregation in humid environments, resulting in decreased catalytic performance. Hydration of alumina supports also leads to a significant decrease in specific surface area and collapse of the pore structure. The hydrophobic effect has been proven effective in many catalytic fields. Catalytic activity, product selectivity, and catalyst stability are closely related to the hydrophobicity of the catalyst. Hydrophobic catalysts have broad application prospects and market demand in organic synthesis and chemical engineering, petrochemicals, environmental protection and pollution control, energy conversion and storage, carbon dioxide capture and conversion, material synthesis and polymerization reactions, catalytic degradation and recovery, and other fields. Therefore, adjusting the hydrophilicity or hydrophobicity of the catalyst surface to avoid or reduce the side effects of water is crucial for industrial production.
[0003] In recent years, improving the hydrophobicity of catalysts through surface treatment has become an effective means of enhancing catalyst performance. This hydrophobic modification is particularly important in systems where reactions are susceptible to H2O. Taking methanol reforming for hydrogen production as an example, the produced hydrogen typically contains 0.5-2% CO and 10-20% H2O. In practical industrial applications, preferentially oxidizing CO in H2 (CO-PROX) and reducing the CO concentration to the ppm level remains a very challenging task. Under the reaction conditions of the CO-PROX process, H2O in the hydrogen-rich gas condenses in the micropores of the catalyst surface to form a liquid film, inhibiting the diffusion and adsorption of reactants. This hinders the effective interaction between reactants and catalytic sites, thereby reducing the overall catalytic activity. Therefore, the hydrophobicity of the catalyst surface is crucial for ensuring the long-term stability of CO-PROX catalysts under actual industrial conditions. Through hydrophobic treatment, the catalyst can avoid the condensation and coating of water molecules on the catalyst surface, preventing the active sites from being covered and extending the catalyst's lifespan. However, most current hydrophobic modification methods primarily modify the catalyst surface, inevitably covering some of the metal active sites on the catalyst surface, leading to a decrease in catalyst activity. Therefore, developing an environmentally friendly, economical hydrophobic modification method that does not interfere with the catalyst's active sites is of great significance for the preferential carbon monoxide oxidation reaction under actual industrial conditions.
[0004] Therefore, given the requirements of industrial applications for catalyst operating cycles and lifespan, there is a need to provide a hydrophobic modification method that can be mass-produced to reduce or avoid the influence of water molecules on hydrophilic catalysts at low temperatures. Summary of the Invention
[0005] One objective of this application is to perform hydrophobic modification of Pt / Al2O3 catalysts at low temperatures, under which the hydrophobically modified catalysts maintain excellent catalytic performance for CO oxidation in more complex environments. For example, they exhibit good catalytic performance at low temperatures under hydrogen-rich, CO2-rich, and / or water-rich conditions.
[0006] Another objective of this application is to extend the service life of the hydrophobically modified Pt / Al2O3 catalyst.
[0007] A method for hydrophobic modification of a catalyst for selective CO oxidation includes: mixing a Pt / Al2O3 catalyst with a hydrophobic modifier in an organic solvent at a temperature less than or equal to 30°C to obtain a mixture; and filtering and drying the mixture to obtain a modified Pt / Al2O3 catalyst.
[0008] Hydrophobic modifiers include organosilanes, esters, and one or more fatty acids in mixture.
[0009] The catalyst prepared by the above method is applied to the CO oxidation reaction system.
[0010] This application utilizes the aforementioned low-temperature hydrophobic method to modify the Pt / Al2O3 catalyst, thereby improving the CO conversion rate of the catalyst in the low-temperature range. The modified catalyst exhibits higher activity and longer service life.
[0011] This invention achieves the technical effect of hydrophobic modification of the support surface without affecting the catalytic performance of the active center by selectively controlling the reaction kinetics between the modified molecules and the defect sites of Al2O3 on the support through regulating the molecular concentration of the hydrophobic modified atmosphere, while inhibiting its interaction with the active Pt sites.
[0012] The hydrophobic modification method provided by this invention is simple in steps, highly operable, and has mild modification conditions, and can establish a stable hydrophobic surface in a short time. Attached Figure Description
[0013] Figure 1 The image shows the catalytic stability of the catalyst prepared in Example 1.
[0014] Figure 2 The contact angle of the Pt / Al2O3 catalyst without hydrophobic modification in the examples is the test result.
[0015] Figure 3 The relationship between the total carbon number and contact angle of the modifier in this application.
[0016] Figure 4 Example 1: FTIR comparison of Pt / Al2O3 catalyst and catalyst support before and after hydrophobic modification. Detailed Implementation
[0017] The hydrophobic modification method of the catalyst for selective CO oxidation of the present invention is described in further detail below. This does not limit the scope of protection of this application, which is defined by the claims. Certain specific details disclosed provide a comprehensive understanding of the various disclosed embodiments. However, those skilled in the art will recognize that embodiments can be implemented using other materials, etc., without employing one or more of these specific details.
[0018] Unless the context otherwise requires, the terms “comprising” and “including” in the specification and claims shall be understood as open-ended and inclusive, meaning “including, but not limited to”.
[0019] The terms "implementation," "an implementation," "another implementation," or "certain implementations" used in this specification refer to specific features, structures, or characteristics described in relation to the implementation, which are included in at least one implementation. Therefore, "implementation," "an implementation," "another implementation," or "certain implementations" do not necessarily all refer to the same implementation. Furthermore, specific features, structures, or characteristics can be combined in any way within one or more implementations. Each feature disclosed in this specification can be replaced by any alternative feature that provides the same, equivalent, or similar purpose. Therefore, unless otherwise specified, the disclosed features are merely general examples of equivalent or similar features.
[0020] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Experimental methods in the following embodiments, unless otherwise specified, are generally performed under conventional conditions or as recommended by the manufacturer. Unless otherwise stated, all percentages, ratios, proportions, or parts are by weight.
[0021] The units in the weight-volume percentages of this invention are well known to those skilled in the art, for example, referring to the weight of the solute in 100 ml of solution.
[0022] In this invention, the concentration unit "M" of the solution represents mol / L.
[0023] In this application, "hydrogen-rich" refers to a mixed gas containing more than 50% hydrogen, or even more than 60%.
[0024] In this application, "CO2 rich" refers to a CO2 content in the mixed gas that is 10% or more, or even 17% or more.
[0025] In this application, "water-rich" refers to a water content in the mixed gas of 10% or more, or even 17% or more.
[0026] In the description of numerical ranges in this application, the range above or below a certain value includes values equal to that value, and the range between two numerical ranges includes values at both endpoints.
[0027] The element content in the catalyst of this application refers to the percentage of the mass of the metal element in the total mass of the catalyst.
[0028] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as are familiar to those skilled in the art. Furthermore, any methods and materials similar to or equivalent to those described herein may be applied to the methods of this invention. The preferred embodiments and materials described herein are for illustrative purposes only.
[0029] This application presents a hydrophobic modification method for Pt / Al2O3 catalysts, which improves the catalyst's water resistance while enabling efficient and selective CO removal under practical industrial conditions. This method achieves a water contact angle of approximately 40°-160° for the catalyst. By adjusting the type of modifier, the catalyst can exhibit excellent catalytic performance and stability over a wide operating temperature range (80-200℃).
[0030] A method for hydrophobic modification of a catalyst for selective CO oxidation includes: mixing a Pt / Al2O3 catalyst with a hydrophobic modifier in an organic solvent at a temperature less than or equal to 30°C to obtain a mixture; and filtering and drying the mixture to obtain a modified Pt / Al2O3 catalyst.
[0031] Optionally, the Pt / Al2O3 catalyst and the hydrophobic modifier are mixed in an organic solvent at a temperature of room temperature to 30°C for more than 12 hours. Preferably, the Pt / Al2O3 catalyst and the hydrophobic modifier are mixed in an organic solvent at a temperature of room temperature to 30°C for 24 hours.
[0032] Typically, "room temperature" ranges from 17 to 25°C.
[0033] Alternatively, γ-Al2O3 can be used as the support.
[0034] When the modification time is higher than 24 hours, the hydrophobicity of the catalyst is not affected. When the modification time is lower than 24 hours (especially lower than 12 hours), the modifier does not have enough time to contact the catalyst surface and react. The hydrophobicity of the catalyst will decrease as the time shortens. The degree of decrease varies depending on the type of modifier. The shorter the carbon chain length of the modifier, the greater the impact of the modification time on the hydrophobicity.
[0035] The organic solvent is selected from one or a mixture of two or more of cyclohexane, methylcyclohexane, toluene, ethanol, and acetone.
[0036] Optionally, the organic solvent may be selected from one or more of cyclohexane, toluene, and methylcyclohexane.
[0037] In the preferred embodiment, cyclohexane is selected as the organic solvent.
[0038] When cyclohexane is used as an organic solvent to mix with Pt / Al2O3 catalysts, virtually no additional heating is required; mixing can be done at ambient temperature. However, when hydrophobic treatment is performed at 40°C, cyclohexane evaporates rapidly, making it difficult to create a stable modification environment. Furthermore, excessively high temperatures can cause over-reaction of the modifier molecules (cyclohexane), displacing the active sites of the catalyst. Compared to organic solvents such as toluene and acetone, cyclohexane, as a hydrophobic solvent, allows for lower CO residue levels in Pt / Al2O3 catalysts. It also results in less pollution, lower cost, and lower toxicity, making it a superior hydrophobic modification organic solvent.
[0039] In some embodiments, the organosilane includes one or a mixture of two or more of methyltrimethoxysilane, ethyltrimethoxysilane, hexyltrimethoxysilane, octyltrimethoxysilane, dodecyltrimethoxysilane, octadecyltrimethoxysilane, ethyltrichlorosilane, hexyltrichlorosilane, and octadecyltrichlorosilane; the ester includes one or a mixture of two or more of hexadecyl acrylate, dodecyl acrylate, and ethyl octanoate; and the fatty acid includes one or a mixture of two or more of stearic acid, palmitic acid, oleic acid, and lauric acid.
[0040] Optionally, the hydrophobic modifier is selected from dodecyltrimethoxysilane and / or octadecyltrimethoxysilane.
[0041] In some embodiments, the Pt element content in the Pt / Al2O3 catalyst is 0.1-5.0 wt%.
[0042] In some embodiments, the amount of hydrophobic modifier added is 0.1-12.0 mmol / g of catalyst by mass. That is, 0.1-12.0 mmol of hydrophobic modifier is used to modify each gram of catalyst.
[0043] Optionally, the hydrophobic modifier is an organosilane, and the ratio of organosilane to catalyst is 0.1-2.0 mmol / g. Preferably, the ratio of organosilane to catalyst is 0.5-1.3 mmol / g (more preferably 0.5-1.0 mmol / g).
[0044] The hydrophobic modifier is an ester or fatty acid, and the ratio of hydrophobic modifier to catalyst is 6.0-12.0 mmol / g.
[0045] In some embodiments, a Pt / Al2O3 catalyst is added to a certain amount of organic solvent, and a modifier is added thereto to form a mixture.
[0046] In the mixture, the mass / volume ratio of Pt / Al2O3 catalyst to organic solvent is 1:(18-21), preferably 1:20.
[0047] At the above ratio, a sufficient and relatively stable modification environment is provided for the Pt / Al2O3 catalyst during modification, reducing the impact of cyclohexane volatilization and uneven dispersion of the modifier on the modification results.
[0048] Optionally, the mixture can be ultrasonicated under ultrasonic conditions to ensure uniform dispersion of the modifier. Preferably, the ultrasonication time is 30-90 minutes.
[0049] In some embodiments, the solid filter residue is washed several times with anhydrous ethanol before drying. This washes away any residual organic solvent.
[0050] The drying temperature is between 60-100℃. Preferably, the drying temperature is about 80℃.
[0051] There is no time limit for drying, as long as the water content of the hydrophobically modified solid material is controlled to a certain level.
[0052] In the modification process described in this invention, the hydrophobic modification process does not destroy the initial morphology of the catalyst. That is, the catalyst is strip-shaped before modification and remains strip-shaped after modification.
[0053] In some embodiments, the modified Pt / Al2O3 catalyst is reduced in a reducing atmosphere.
[0054] The reduction treatment temperature is in the range of 150-200℃.
[0055] The reduction treatment temperature can be selected within the range of 150-200℃. For example, 200℃.
[0056] The reduction process can also be carried out in the reaction vessel before the catalytic reaction.
[0057] The reducing gas is a mixture containing hydrogen or CO.
[0058] Optionally, the gas mixture may also contain nitrogen or other gases that do not participate in the reaction.
[0059] By controlling the above-mentioned hydrophobic modification methods, different hydrophobic effects and different properties can be achieved at angles of approximately 40 to 160°.
[0060] In some embodiments, the preparation method of Pt / Al2O3 catalyst includes: heating a precursor solution of metallic Pt under alkaline conditions to form a colloidal solution; mixing the Pt-containing colloidal solution with an Al2O3 support, adjusting the pH to about 9, and precipitating a mixture; and washing and drying the precipitate obtained after filtration to obtain the Pt / Al2O3 catalyst.
[0061] The precursor solution of metallic Pt forms a colloidal solution under alkaline conditions at 100-130℃.
[0062] Optionally, the solvent in the precursor solution of metallic Pt is ethylene glycol.
[0063] Alternatively, a Pt-containing colloidal solution can be mixed with an Al2O3 support at approximately 70-100°C.
[0064] The catalyst prepared by the above method, after hydrophobic modification, exhibits better catalytic performance for CO oxidation under hydrogen-rich and water-rich conditions, and has a longer service life.
[0065] On the other hand, the catalyst prepared by any of the above schemes is used in the reaction system for oxidizing CO to produce CO2.
[0066] That is, a method for oxidizing CO to prepare CO2 includes reacting the reactants CO and O2 with a catalyst prepared by any of the above schemes to obtain CO2 gas at a temperature not lower than 80°C.
[0067] That is, CO can be completely oxidized within a temperature range of 80-200℃.
[0068] The reaction raw materials also include water (water vapor). The water content is above 10 vol%.
[0069] In some embodiments, the reaction feedstock also includes hydrogen and / or CO2.
[0070] The reaction process for producing CO from CO exhibits excellent CO catalytic oxidation at temperatures above 80°C in an atmosphere containing water, thus improving the CO conversion rate in the low-temperature range of the catalyst. It is unaffected by moisture in the atmosphere, resulting in a long catalyst lifespan.
[0071] The hydrogen content in the reaction raw materials can be higher than 50 vol%.
[0072] Selectable mass hourly space velocity (MHSV) is 2000-80000 ml·g. -1 ·h -1 Preferably, the mass hourly space velocity (MSV) is 5000-30000 ml·g. -1 ·h -1 .
[0073] The CO selective oxidation catalyst modified by the present application can operate under water-rich conditions (such as further hydrogen enrichment and / or CO2 enrichment) at relatively low temperatures (T). 100 Not lower than 80℃), and over a wider temperature range (i.e., ΔT) 100It exhibits excellent CO catalytic oxidation activity (above 100℃), with a temperature range reaching 120℃. The catalyst has a low content of precious metals, reducing production costs. It can reduce CO to the ppb level and operate stably for 100 hours without deactivation (e.g., Figure 1 Furthermore, the catalyst exhibits good tolerance to impurities such as carbon dioxide and water.
[0074] The catalyst of the present invention and its catalytic effect are further illustrated below with specific embodiments. All substances used in the following embodiments are chemically pure standards.
[0075] Preparation method of Pt / Al2O3 catalyst:
[0076] First, prepare 50 ml of ethylene glycol solution containing 1.93 mM H₂PtCl₆·6H₂O, and add it to 50 ml of ethylene glycol solution containing 0.5 M NaOH. Then, heat at 120 °C for 3 hours under an inert Ar atmosphere until the solution turns dark brown and forms a colloidal solution without any precipitate, thus preparing uniformly distributed Pt nanoparticles. Subsequently, a certain amount of the uniformly distributed Pt nanoparticle colloidal solution is stirred at 80 °C, and 1.0 g of γ-Al₂O₃ powder is added during stirring. The pH of the solution is adjusted to 9 with 0.5 M NaOH solution. The resulting precipitate is filtered, washed with 2 L of high-temperature ultrapure water, and then dried overnight at 80 °C (expressed as Pt / Al₂O₃, theoretical Pt loading is 1 wt%). The dried catalyst powder is then extruded into strips using conventional molding techniques to obtain strip-shaped Pt / Al₂O₃ catalysts.
[0077] The Pt / Al2O3 catalyst samples used in the following examples and comparative examples were all prepared by the above preparation method.
[0078] Example 1
[0079] 2.5 g of the shaped Pt / Al₂O₃ catalyst sample was added to 50 mL of cyclohexane, and 0.5 mmol / g cat amount of octadecyltrimethoxysilane was added using a pipette, followed by thorough mixing. The mixture was then sonicated for 1 h. Afterward, it was stirred at 30 °C for 24 h. Following stirring, the mixture was filtered to obtain the modified sample, which was then washed three times with anhydrous ethanol. After washing, the sample was dried in an 80 °C oven for 8 h to obtain the modified product.
[0080] Example 2
[0081] 2.5 g of the shaped Pt / Al₂O₃ catalyst sample was added to 50 mL of cyclohexane, and 0.5 mmol / g cat dose of dodecyltrimethoxysilane was added using a pipette, followed by thorough mixing. The mixture was then sonicated for 1 h. Afterward, it was stirred at 30 °C for 24 h. Following stirring, the mixture was filtered to obtain the modified sample, which was then washed three times with anhydrous ethanol. After washing, the sample was dried in an 80 °C oven for 8 h to obtain the modified product.
[0082] Example 3
[0083] 2.5 g of the shaped Pt / Al₂O₃ catalyst sample was added to 50 mL of cyclohexane, and 0.5 mmol / g cat amount of octyltrimethoxysilane was added using a pipette, followed by thorough stirring. The mixture was then sonicated for 1 h. Afterward, it was stirred at 30 °C for 24 h. Following stirring, the mixture was filtered to obtain the modified sample, which was then washed three times with anhydrous ethanol. After washing, the sample was dried in an 80 °C oven for 8 h to obtain the modified product.
[0084] Example 4
[0085] 2.5 g of the shaped Pt / Al₂O₃ catalyst sample was added to 50 mL of cyclohexane, and 0.5 mmol / g cat amount of hexyltrimethoxysilane was added using a pipette, followed by thorough mixing. The mixture was then sonicated for 1 h. Afterward, it was stirred at 30 °C for 24 h. Following stirring, the mixture was filtered to obtain the modified sample, which was then washed three times with anhydrous ethanol. After washing, the sample was dried in an 80 °C oven for 8 h to obtain the modified product.
[0086] Example 5
[0087] 2.5 g of the shaped Pt / Al₂O₃ catalyst sample was added to 50 mL of cyclohexane, and 0.5 mmol / g cat amount of ethyltrimethoxysilane was added using a pipette, followed by thorough mixing. The mixture was then sonicated for 1 h. Afterward, it was stirred at 30 °C for 24 h. Following stirring, the mixture was filtered to obtain the modified sample, which was then washed three times with anhydrous ethanol. After washing, the sample was dried in an 80 °C oven for 8 h to obtain the modified product.
[0088] Example 6
[0089] 2.5 g of the shaped Pt / Al₂O₃ catalyst sample was added to 50 mL of cyclohexane, and 0.5 mmol / g cat amount of methyltrimethoxysilane was added using a pipette, followed by thorough mixing. The mixture was then sonicated for 1 h. Afterward, it was stirred at 30 °C for 24 h. Following stirring, the mixture was filtered to obtain the modified sample, which was then washed three times with anhydrous ethanol. After washing, the sample was dried in an 80 °C oven for 8 h to obtain the modified product.
[0090] Example 7
[0091] 2.5 g of the shaped Pt / Al₂O₃ catalyst sample was added to 50 mL of toluene, and 0.5 mmol / g cat of octadecyltrimethoxysilane was added using a pipette, followed by thorough mixing. The mixture was then sonicated for 1 h. Afterward, it was stirred at 30 °C for 24 h. Following stirring, the mixture was filtered to obtain the modified sample, which was then washed five times with anhydrous ethanol. After washing, the sample was dried in an 80 °C oven for 8 h to obtain the modified product.
[0092] Example 8
[0093] 2.5 g of the shaped Pt / Al₂O₃ catalyst sample was added to 50 mL of methylcyclohexane, and 0.5 mmol / g cat amount of octadecyltrimethoxysilane was added using a pipette, followed by thorough mixing. The mixture was then sonicated for 1 h. Afterward, it was stirred at 30 °C for 24 h. Following stirring, the mixture was filtered to obtain the modified sample, which was then washed five times with anhydrous ethanol. After washing, the sample was dried in an 80 °C oven for 8 h to obtain the modified product.
[0094] Example 9
[0095] 2.5 g of the shaped Pt / Al₂O₃ catalyst sample was added to 50 mL of cyclohexane, and 0.5 mmol / g cat amount of octadecyltrichlorosilane was added using a pipette, followed by thorough mixing. The mixture was then sonicated for 1 h. Afterward, it was stirred at 30 °C for 24 h. Following stirring, the mixture was filtered to obtain the modified sample, which was then washed five times with anhydrous ethanol. After washing, the sample was dried in an 80 °C oven for 8 h to obtain the modified product.
[0096] Example 10
[0097] 2.5 g of the shaped Pt / Al₂O₃ catalyst sample was added to 50 mL of cyclohexane, and 0.5 mmol / g cat dose of hexyltrichlorosilane was added using a pipette, followed by thorough mixing. The mixture was then sonicated for 1 h. Afterward, it was stirred at 30 °C for 24 h. Following stirring, the mixture was filtered to obtain the modified sample, which was then washed five times with anhydrous ethanol. After washing, the sample was dried in an 80 °C oven for 8 h to obtain the modified product.
[0098] Example 11
[0099] 2.5 g of the shaped Pt / Al₂O₃ catalyst sample was added to 50 mL of cyclohexane, and 0.5 mmol / g cat amount of ethyltrichlorosilane was added using a pipette, followed by thorough mixing. The mixture was then sonicated for 1 h. Afterward, it was stirred at 30 °C for 24 h. Following stirring, the mixture was filtered to obtain the modified sample, which was then washed five times with anhydrous ethanol. After washing, the sample was dried in an 80 °C oven for 8 h to obtain the modified product.
[0100] Example 12
[0101] 2.5 g of the shaped Pt / Al₂O₃ catalyst sample was added to 50 mL of cyclohexane, and 6 mmol / g cat of hexadecyl acrylate was added using a pipette, followed by thorough mixing. The mixture was then sonicated for 1 h. Afterward, it was stirred at 30 °C for 24 h. Following stirring, the mixture was filtered to obtain the modified sample, which was then washed five times with anhydrous ethanol. After washing, the sample was dried in an 80 °C oven for 8 h to obtain the modified product.
[0102] Example 13
[0103] 2.5 g of the shaped Pt / Al₂O₃ catalyst sample was added to 50 mL of cyclohexane, and 6 mmol / g cat of dodecyl acrylate was added using a pipette, followed by thorough mixing. The mixture was then sonicated for 1 h. Afterward, it was stirred at 30 °C for 24 h. Following stirring, the mixture was filtered to obtain the modified sample, which was then washed three times with anhydrous ethanol. After washing, the sample was dried in an 80 °C oven for 8 h to obtain the modified product.
[0104] Example 14
[0105] 2.5 g of the shaped Pt / Al₂O₃ catalyst sample was added to 50 mL of cyclohexane, and 6 mmol / g cat amount of ethyl octanoate was added using a pipette, followed by thorough mixing. The mixture was then sonicated for 1 h. Afterward, it was stirred at 30 °C for 24 h. Following stirring, the mixture was filtered to obtain the modified sample, which was then washed three times with anhydrous ethanol. After washing, the sample was dried in an 80 °C oven for 8 h to obtain the modified product.
[0106] Example 15
[0107] 2.5 g of the shaped Pt / Al₂O₃ catalyst sample was added to 50 mL of acetone, and 6 mmol / g cat amount of stearic acid was added using a pipette, followed by thorough mixing. The mixture was then sonicated for 1 h. Afterward, it was stirred at 30 °C for 24 h. Following stirring, the mixture was filtered to obtain the modified sample, which was then washed three times with anhydrous ethanol. After washing, the sample was dried in an 80 °C oven for 8 h to obtain the modified product.
[0108] Example 16
[0109] 2.5 g of the shaped Pt / Al₂O₃ catalyst sample was added to 50 mL of ethanol, and 12 mmol / g cat amount of palmitic acid was added to the mixture using a pipette, followed by thorough stirring. The mixture was then sonicated for 1 h. Afterward, it was stirred at 30 °C for 24 h. Following stirring, the mixture was filtered to obtain the modified sample, which was then washed three times with anhydrous ethanol. After washing, the sample was dried in an 80 °C oven for 8 h to obtain the modified product.
[0110] Example 17
[0111] 2.5 g of the shaped Pt / Al₂O₃ catalyst sample was added to 50 mL of ethanol, and 12 mmol / g cat amount of oleic acid was added to the mixture using a pipette, followed by thorough stirring. The mixture was then sonicated for 1 h. Afterward, it was stirred at 30 °C for 24 h. Following stirring, the mixture was filtered to obtain the modified sample, which was then washed three times with anhydrous ethanol. After washing, the sample was dried in an 80 °C oven for 8 h to obtain the modified product.
[0112] Example 18
[0113] 2.5 g of the shaped Pt / Al₂O₃ catalyst sample was added to 50 mL of ethanol, and 12 mmol / g cat amount of lauric acid was added using a pipette, followed by thorough mixing. The mixture was then sonicated for 1 h. Afterward, it was stirred at 30 °C for 24 h. Following stirring, the mixture was filtered to obtain the modified sample, which was then washed three times with anhydrous ethanol. After washing, the sample was dried in an 80 °C oven for 8 h to obtain the modified product.
[0114] Comparative Example 1
[0115] 2.5 g of the shaped Pt / Al₂O₃ catalyst sample was added to 50 mL of cyclohexane, and 0.5 mmol / g cat amount of octadecyltrimethoxysilane was added using a pipette, followed by thorough mixing. The mixture was then sonicated for 1 h. Afterward, it was stirred at 60 °C for 24 h. Following stirring, the mixture was filtered to obtain the modified sample, which was then washed three times with anhydrous ethanol. After washing, the sample was dried in an 80 °C oven for 8 h to obtain the modified product.
[0116] Comparative Example 2
[0117] 2.5 g of the prepared Pt / CeO2 catalyst sample was added to 50 mL of cyclohexane, and 0.5 mmol / g cat amount of octadecyltrimethoxysilane was added using a pipette, followed by thorough mixing. The mixture was then sonicated for 1 h, followed by stirring at room temperature for 24 h. After stirring, the mixture was filtered to obtain the modified sample, which was then washed three times with anhydrous ethanol. After washing, the sample was dried in an 80 °C oven for 8 h to obtain the modified product.
[0118] The preparation method of Pt / CeO2 catalyst adopts the same method as the preparation method of Pt / Al2O3 catalyst, except that CeO2 powder is used instead of Al2O3 powder as the catalyst support.
[0119] Comparative Example 3
[0120] 2.5 g of the shaped Pt / Al₂O₃ catalyst sample was added to 50 mL of cyclohexane, and 0.1 mmol / g cat amount of octadecyltrimethoxysilane was added using a pipette, followed by thorough stirring. The mixture was then sonicated for 1 h. Afterward, it was stirred at 30 °C for 24 h. Following stirring, the mixture was filtered to obtain the modified sample, which was then washed three times with anhydrous ethanol. After washing, the sample was dried in an 80 °C oven for 8 h to obtain the modified product.
[0121] Comparative Example 4
[0122] 2.5 g of the shaped Pt / Al₂O₃ catalyst sample was added to 50 mL of cyclohexane, and 1.5 mmol / g cat amount of octadecyltrimethoxysilane was added using a pipette, followed by thorough stirring. The mixture was then sonicated for 1 h. Afterward, it was stirred at 30 °C for 24 h. Following stirring, the mixture was filtered to obtain the modified sample, which was then washed three times with anhydrous ethanol. After washing, the sample was dried in an 80 °C oven for 8 h to obtain the modified product.
[0123] Comparative Example 5
[0124] 2.5 g of the shaped Pt / Al₂O₃ catalyst sample was added to 50 mL of cyclohexane, and 2.0 mmol / g cat amount of octadecyltrimethoxysilane was added using a pipette, followed by thorough mixing. The mixture was then sonicated for 1 h. Afterward, it was stirred at 30 °C for 24 h. Following stirring, the mixture was filtered to obtain the modified sample, which was then washed three times with anhydrous ethanol. After washing, the sample was dried in an 80 °C oven for 8 h to obtain the modified product.
[0125] Experimental Example 1
[0126] The contact angles of the hydrophobic Pt-based catalysts prepared in Examples 1-18 and Comparative Examples 1-2 were measured using a DSA100M (Krüss instrument) equipped with a saturated water vapor environment chamber. The results are shown in Table 1.
[0127] Table 1
[0128]
[0129]
[0130] As shown in Table 1, the contact angles of the modified Pt / Al2O3 catalyst samples obtained in Examples 1-6 were measured using a contact angle meter, and compared with those of the unmodified Pt / Al2O3 catalyst sample (…). Figure 3 Compared to the previous method, the modified Pt / Al2O3 catalyst sample exhibited improved hydrophobicity. The relationship between the total carbon number of the modifier and the hydrophobic angle is shown in the figure below. Figure 3 As shown, the results indicate that, at the same hydrophobic treatment concentration, the hydrophobic effect is better as the total carbon number of the modifier molecule increases.
[0131] As shown in Table 1, the contact angles of the modified Pt / Al2O3 catalyst samples obtained in Examples 7-8 were measured using a contact angle meter. Compared to the 142.3° hydrophobic angle of the Pt / Al2O3 catalyst sample treated with cyclohexane, the hydrophobic angle provided by toluene was 140.5°, and that provided by methylcyclohexane was 132.2°. This indicates that the hydrophobic effects provided by toluene and cyclohexane are not significantly different, while the hydrophobic angle provided by methylcyclohexane is approximately 10° lower than that of both toluene and cyclohexane.
[0132] As shown in Table 1, the contact angles of the modified Pt / Al2O3 catalyst samples obtained in Examples 9-11 were measured using a contact angle meter, and compared with those of the unmodified Pt / Al2O3 catalyst samples (…). Figure 2 Compared to other catalysts, the modified Pt / Al2O3 catalyst sample exhibited improved hydrophobicity. Similar to the trend observed with trimethoxysilane, the higher the total carbon number of the modifier, the better the modification effect.
[0133] As shown in Table 1, the contact angles of the modified Pt / Al2O3 catalyst samples obtained in Examples 12-18 were measured using a contact angle meter, and compared with those of the unmodified Pt / Al2O3 catalyst samples (…). Figure 2 Compared to the original, the modified Pt / Al2O3 catalyst sample exhibited improved hydrophobicity. It should be noted that acid or ester modifiers often require acetone or ethanol as an organic solvent to achieve good hydrophobic effects.
[0134] As shown in Table 1, the contact angles of the modified Pt / Al2O3 catalyst samples obtained in Comparative Example 1 were measured using a contact angle meter. When hydrophobic treatment was performed at a relatively high temperature (such as 60℃), cyclohexane, due to its low boiling point, evaporated rapidly during the modification process and was difficult to condense quickly, failing to provide a stable modification environment. Consequently, the hydrophobicity of the catalyst decreased significantly compared to the result achieved at 30℃. Furthermore, excessively high temperatures can cause over-reaction of the modifier molecules, replacing the active sites of the catalyst.
[0135] As shown in Table 1, the contact angles of the modified Pt / CeO2 catalyst samples obtained in Comparative Example 2 were measured using a contact angle meter. When hydrophobic treatment was performed using a non-Al2O3 support such as CeO2, the hydrophobic modification effect decreased significantly.
[0136] As shown in Table 1, under the hydrophobic treatment concentration of 0.1 mmol / g cat, the static water contact angle of the modified catalyst was only 120.5°, significantly lower than the contact angle values of samples treated with concentrations of 0.5 mmol / g cat and above, with a difference of more than 20.0°. This difference stems from the insufficient coverage of the surface modifier at lower concentrations, which prevents the formation of a complete hydrophobic layer, resulting in higher surface energy. In contrast, higher concentration treatments can achieve a surface coverage of >95%, forming a uniform low surface energy modified layer.
[0137] Experimental Example 2
[0138] The hydrophobic Pt / Al2O3 catalysts prepared in Examples 1-18 and Comparative Examples 3-5 were tested for their selective CO oxidation performance under hydrogen-rich conditions. The method was as follows: 0.6 g of the hydrophobically modified Pt / Al2O3 catalyst was packed into a fixed-bed reactor. The feed gas composition was 60% H2, 1% CO, 1% O2, 20% CO2, and 18% H2O. The total gas flow rate was 100 ml / min, and the mass hourly space velocity (MSV) was 5000 mL·h. -1 ·gcat -1The reaction temperature range is 80–200℃, and the product composition is analyzed online using gas chromatography. The CO conversion rate is calculated using the formula: CO conversion rate = (initial CO content - tail gas CO content) / initial CO content × 100%. The temperature range ΔT at which the catalyst achieves complete CO conversion (approximately 100% conversion rate) and the minimum temperature T for complete CO conversion are also determined. 100 See Table 2.
[0139] Table 2
[0140]
[0141]
[0142] As shown in Table 2, the performance of hydrophobically modified Pt / Al2O3 catalysts varies depending on the type of modifier. Among them, octadecyltrimethoxysilane and dodecyltrimethoxysilane provide a wider temperature range for complete CO conversion than other modifiers, enabling the catalysts to exhibit near-complete CO conversion performance advantages in the range of 80–200℃, and the contact angle of the modified catalysts is above 120°.
[0143] As shown in Table 2, at a modification concentration of 0.1 mmol / g cat, the catalyst's insufficient surface hydrophobicity (contact angle θ = 120.5°) led to competitive adsorption of water molecules on the surface at low temperatures (<110℃), resulting in a decrease in CO conversion. When the modification concentration was increased to 1.5-2.0 mmol / g cat, the coverage of defect sites on the Al2O3 support surface was too high, and excessive hydrophobic molecules covered the Pt active sites through physical adsorption (coverage >30%), causing a significant decrease in CO conversion at high temperatures (>120℃). The above results show that the optimal modification concentration (0.5 mmol / g cat) can maintain Pt site accessibility (coverage <5%) while ensuring surface hydrophobicity (θ >= 140.0°), achieving a CO conversion rate >99% across the entire temperature range (80-200℃).
[0144] Experimental Example 3
[0145] The CO residue levels in the CO selective oxidation performance tests of the hydrophobic Pt / Al₂O₃ catalysts prepared in Examples 1, 7, and 8 under hydrogen-rich conditions were compiled. The residue levels were determined by online gas chromatography analysis of the reaction products and recorded. The CO concentration R of the catalyst at different temperatures T was also analyzed. T See Table 3, for example R 160 This represents the amount of CO residue at 160℃.
[0146] Table 3
[0147] <![CDATA[R 160 (ppm)]]> <![CDATA[R 180 (ppm)]]> <![CDATA[R 200 (ppm)]]> Example 1 14.5 12.3 15.2 Example 7 29.1 15.4 46.6 Example 8 29.5 35.6 63.1
[0148] As shown in Table 3, the Pt / Al2O3 catalyst treated with cyclohexane as a solvent for hydrophobic treatment can achieve a lower CO residue at high temperatures than toluene solvent. Moreover, cyclohexane causes less pollution, has lower cost and lower toxicity, making it a superior hydrophobically modified organic solvent.
[0149] Experiment Example 4
[0150] This experimental example tests the stability of the catalyst prepared in Example 1. The selective CO oxidation performance of the modified Pt / Al₂O₃ catalyst and the unmodified Pt / Al₂O₃ catalyst from Example 1 under hydrogen-rich conditions was tested under the same conditions as in Example 2. The difference from Example 2 is that the reaction temperature was 80°C.
[0151] Results of the attached Figure 1 As shown, in the first 30 hours of operation, the performance of the modified catalyst Pt / Al2O3 and the unmodified catalyst Pt / Al2O3 in converting CO was basically the same. As the reaction continued, the modified catalyst Pt / Al2O3 in Example 1 maintained stable catalytic performance within 100 hours. However, the catalytic performance of the unmodified catalyst Pt / Al2O3 gradually decreased after 30 hours.
[0152] Figure 4 This is a comparative analysis of the Fourier transform infrared (FTIR) spectra of the Pt / Al₂O₃ catalyst and its support before and after hydrophobic modification in Example 1. The unmodified catalyst at 3497 cm⁻¹... - The characteristic absorption peak at position 1 can be attributed to water molecules adsorbed from the air and the stretching vibrations of hydroxyl groups (-OH) on the support surface. After hydrophobic modification, the intensity of this peak significantly decreased, indicating a reduction in surface hydrophilicity. Furthermore, the modified catalyst showed a peak intensity at 2926 cm⁻¹. - 1 and 2856cm - The presence of both an asymmetric stretching vibration peak for the -CH2- group and a symmetric stretching vibration peak for the -CH3 group at position 1 confirms the successful grafting of octadecyl groups onto the catalyst surface. Simultaneously, a peak at 1061 cm⁻¹ related to the Al-O-Al bond stretching vibration was observed. -1 The broadening of the infrared characteristic peaks indicates the formation of Si-O-Al bonds, further verifying the silanization reaction during the hydrophobic modification process. These results collectively demonstrate that hydrophobic modification effectively reduces the surface energy of the catalyst through chemical bonding and introduces hydrophobic alkyl chains, thereby achieving hydrophobic functionalization of the catalyst.
[0153] In summary, this invention relates to a method for modifying the hydrophobicity of a catalyst surface. The method is flexible; the silane reagent is not limited to one type, and can be selected from trimethoxysilanes and trichlorosilanes with different carbon chain lengths, ranging from methyl to octadecyl, to meet the hydrophobic requirements of the catalyst without affecting its original active sites. This invention is also applicable when the hydrophobic modifier is changed from a silane coupling agent to an ester or acid-based hydrophobic modifier. Furthermore, the organic solvent used in the modification process can be selected from toluene, cyclohexane, methylcyclohexane, acetone, and ethanol, all of which provide a certain degree of hydrophobic effect. Among them, cyclohexane causes less pollution, has lower cost, and lower toxicity, making it a superior organic solvent for hydrophobic modification. If the sample requiring hydrophobic modification is not a catalyst, this invention is also universally applicable when silica and alumina are used as the modified sample for hydrophobic treatment. Finally, the preparation method of this invention is simple, highly operable, and cost-controllable, possessing potential for industrial application.
[0154] The above embodiments are only used to illustrate the basic principles and effects of the present invention and do not limit the specific scope of the present invention. Anyone with relevant technical background can adjust or modify the embodiments without departing from the basic concepts and spirit of the present invention. Therefore, all equivalent modifications or alterations made to the present invention within the scope of this technical field, as long as they do not depart from the core idea of the invention, should be covered by the claims of the present invention.
Claims
1. A method for hydrophobic modification of a catalyst for selective CO oxidation, comprising: The Pt / Al2O3 catalyst and the hydrophobic modifier were mixed in an organic solvent at a temperature of less than or equal to 30°C to obtain a mixture; the mixture was then filtered and dried to obtain the modified Pt / Al2O3 catalyst. Hydrophobic modifiers include one or more of organosilanes, esters, and fatty acids; Preferably, the Pt / Al2O3 catalyst and the hydrophobic modifier are mixed in an organic solvent at a temperature of room temperature to 30°C for more than 12 hours; In a preferred embodiment, the Pt / Al2O3 catalyst and the hydrophobic modifier are mixed in an organic solvent at a temperature of room temperature to 30°C for 24 hours.
2. The method according to claim 1, characterized in that, The organic solvent is selected from one or a mixture of two or more of cyclohexane, methylcyclohexane, toluene, ethanol, and acetone; Preferably, the organic solvent is selected from one or more of cyclohexane, toluene, and methylcyclohexane; More preferably, the organic solvent is selected from cyclohexane.
3. The method according to claim 1, characterized in that, Organosilanes include one or a mixture of two or more of methyltrimethoxysilane, ethyltrimethoxysilane, hexyltrimethoxysilane, octyltrimethoxysilane, dodecyltrimethoxysilane, octadecyltrimethoxysilane, ethyltrichlorosilane, hexyltrichlorosilane, and octadecyltrichlorosilane; esters include one or a mixture of two or more of hexadecyl acrylate, dodecyl acrylate, and ethyl octanoate; fatty acids include one or a mixture of two or more of stearic acid, palmitic acid, oleic acid, and lauric acid. Preferably, the hydrophobic modifier is selected from dodecyltrimethoxysilane and / or octadecyltrimethoxysilane.
4. The method according to any one of claims 1-3, characterized in that, The mass ratio of the hydrophobic modifier to the catalyst is 0.1-12.0 mmol / g; Preferably, the hydrophobic modifier is an organosilane, and the ratio of organosilane to catalyst is 0.1-2.0 mmol / g (preferably 0.5-1.3 mmol / g, more preferably 0.5-1.0 mmol / g); or The hydrophobic modifier is an ester or fatty acid, and the ratio of hydrophobic modifier to catalyst is 6.0-12.0 mmol / g.
5. The method according to any one of claims 1-4, characterized in that, The Pt element content in the Pt / Al2O3 catalyst is 0.1-5.0 wt%. Preferably, the preparation method of Pt / Al2O3 catalyst includes: heating a precursor solution of metallic Pt under alkaline conditions to form a colloidal solution; mixing the Pt-containing colloidal solution with an Al2O3 support, adjusting the pH to about 9, and precipitating a mixture; and washing and drying the precipitate obtained after filtration to obtain the Pt / Al2O3 catalyst.
6. The method according to claim 5, characterized in that, The precursor solution of metallic Pt forms a colloidal solution under alkaline conditions at 100-130℃; Preferably, the solvent in the precursor solution of metallic Pt is ethylene glycol; More preferably, the Pt-containing colloidal solution is mixed with the Al2O3 support at about 70-100°C.
7. The method according to any one of claims 1-5, characterized in that, The mass / volume ratio of Pt / Al2O3 catalyst to organic solvent is 1:(18-21) (preferably 1:20).
8. The method according to any one of claims 1-5, characterized in that, The modified Pt / Al2O3 catalyst was subjected to reduction treatment in a reducing atmosphere; The reduction treatment temperature is in the range of 150-200℃; Preferably, the reduction treatment temperature is in the range of 150-200℃.
9. A method for oxidizing CO to prepare CO2, comprising reacting raw materials CO and O2 under the action of a catalyst prepared by any one of claims 1-8, and obtaining CO2 gas at a temperature not lower than 80°C; Preferably, the reaction temperature is between 80-200℃.
10. The method according to claim 9, characterized in that, The reaction raw materials also include water and hydrogen; Preferably, the water content is above 10 vol%, and the hydrogen content can be above 50 vol%. Preferably, the mass hourly space velocity (MSV) is 2000-80000 ml·g. -1 ·h -1 ; A further preferred option is a mass hourly space velocity (MSV) of 5000-30000 ml·g. -1 ·h -1 .